Evaluation of the cross-section area and flexural strength of fractured rat femurs repaired with titanium and absorbable plates fixation - Paola Corso; Gabrielle Kuchar; Luana Bonetto; Maurício Perussolo; Leonardo Fernandes da Cunha; Carla Castiglia Gonzaga; Rafaela Scariot; Aline Sebastiani (Revista Sul-Brasileira de Odontologia, 2022)
To compare the mechanical strength of rat femur after complete fracture treated absorbable and titanium plates and screws. Material and methods: A total of 10 male Wistar rats were divided in two groups, according to the femoral fracture fixation: titanium (TG) or absorbable plates (AG). A femur fracture was performed in one side after the corresponding plates of each group were adapted and fixated. The euthanasia occurred with 90 days postoperative, and the fracture femurs were compared with the opposite side control group (CG) in the mechanical tests, through the three-point bending flexural test, and the flexural strength was calculated. Using a digital caliper, the cross-section area was calculated. Data were submitted to the statistical analysis, with the significance level of 0.05. Results: The cross-section in the AG was higher than CG (p < 0.001). With respect of flexural strength, the AG was similar with CG (p = 1.00), and the TG showed lower flexural strength when compared with CG (p = 0.006) and with AG (p = 0.042). Conclusion: The group fixed with absorbable plates demonstrated increased cross-section area compared to the control group and increased flexural strength compared to the group fixed with titanium plates.